The world's largest man : a memoir - Key, Harrison Scott (Harper, an imprint of HarperCollins Publishers, 2015)
A humor columnist describes his father, who was more like a remote frontiersman than a 20th-century Mississippian, and the impact he ultimately had on how he related to his own children, despite his polar opposite views and life choices.